Affective reactions and test-driven development: Results from three experiments and a survey - Baldassarre, Maria Teresa; Caivano, Danilo; Fucci, Davide; Romano, Simone; Scanniello, Giuseppe (The Journal of systems and software, 2022)
The research on the claimed effects of Test-Driven Development (TDD) on software quality and developers’ productivity has shown inconclusive results. Some researchers have ascribed such results to the negative affective reactions that TDD would provoke when developers apply it. In this paper, we studied whether and in which phases TDD influences the affective states of developers, who are new to this development approach. To that end, we conducted a baseline experiment and two replications, and analyzed the data from these experiments both individually and jointly. Also, we performed methodological triangulation by means of an explanatory survey, whose respondents were experienced with TDD. The results of the baseline experiment suggested that developers like TDD significantly less, compared to a non-TDD approach. Also, developers who apply TDD like implementing production code significantly less than those who apply a non-TDD approach, while testing production code makes TDD developers significantly less happy. These results were not confirmed in the replicated experiments. We found that the moderator that better explains these differences across experiments is experience (in months) with unit testing, practiced in a test-last manner. The higher the experience with unit testing, the more negative the affective reactions caused by TDD. The results from the survey seem to confirm the role of this moderator. •Experience with unit testing causes more negative affective reactions to TDD.•When learning TDD, it is better to have little experience with unit testing.•Negative affective reactions to TDD can explain contrasting results of TDD research.